Імунологічні та антиоксидантні зміни у осіб, які працюють в умовах дії пилу, що містить кварц - Пилипенко, Н.О.; Pylypenko, N.O. (Харків: Харківський національний університет імені В. Н. Каразіна, 2018)
Pylypenko N. O. Immunological and antioxidant changes in persons working under conditions of action of quartz-containing dust. – Qualification scientific paper, manuscript. Thesis for a Candidate Degree in Biology: Speciality 03.00.13 – Human and Animal Physiology (Biology). –V. N. Karazin Kharkiv National University, the Ministry of Education and Science of Ukraine, Kharkiv, 2018. The results of study of immunological and antioxidant status of persons with hazardous working conditions in foundry are presented in dissertation. After preliminary studies which covered 1017 persons: 742 (73 %) men and 275 women (27 %) that work in hazarders occupational conditions 249 people were selected for more detailed study. They were divided into the following groups: workers that were recognized as healthy (107 persons), 101 workers with bronchial type of ventilation disorders (BTVD) and 41 workers with alveolar type of ventilation disorders (ATVD). Dependence of health on the duration of work in harmful working conditions was analyzed in the seniority groups: up to 10 years, 11-20 years, 21-30 years, more than 30 years. The control group included 30 clinically healthy volunteers who coincided with the main group by age and sex, were not exposed to harmful factors of production and had no history ventilation disorders of lung.
Immunological and antioxidant changes in persons working under conditions of action of quartz-containing dust
У дисертаційній роботі представлено результати вивчення стану імунологічних та антиоксидантних показників осіб, які працюють у шкідливих умовах ливарного виробництва. Після попереднього аналізу показників стану вентиляції легень 1017 працюючих у небезпечних пилових умовах, з яких чоловіків – 742 (73 %), жінок – 275 (27 %), для більш детального вивчення було вибрано 249 осіб, які були розподілені на таки групи: робітники, які були визнані здоровими (107 осіб), працівники з бронхіальним типом зміни вентиляції легень (БТЗВ) (101 особа) та з альвеолярним типом зміни вентиляції легень (АТЗВ) (41 особа). Залежність імунологічних, оксидантних та антиоксидантних показників від тривалості роботи в шкідливих умовах праці була проаналізована в стажевих групах до 10 років, 11-20 років, 21-30 років, більше 30 років. До групи контролю увійшли 30 практично здорових добровольців, які відповідали з основній групі за віком та статтю, не піддавалися впливу шкідливих факторів виробництва та не мали змін вентиляції легень.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::NATURAL SCIENCES; природжений імунітет; гуморальний імунітет; клітинний імунітет; перекисне окиснення ліпідів; антиоксидантний захист; бронхіальний та альвеолярний типи зміни вентиляції легень; пил, що містить кварц; innate immunity; humoral immunity; cellular immunity; peroxide oxidation of lipids; antioxidant protection; bronchial and alveolar types of ventilation disorders; quartz-containing dust